Correlating the rheological and magneto-optical properties of cobalt substituted magnetite ferrofluids (CoxFe1−xFe2O4) with theoretical studies - Blessy Babukutty (17871482) (2023)
Magnetite ferrofluids are widely reported due to their outstanding physicochemical, magnetic and antibacterial properties. This study focusses on the synthesis of magnetite ferrofluids and the effect of Co2+ substitution on their structural, optical, magnetic and rheological properties. An environmental friendly method of co-precipitation is applied to generate CoxFe1−xFe2O4 with variable dopant concentration (x = 0–0.8), which is deeply investigated by structural and functional property analyses of the ferrofluids. X-ray diffraction shows cubic spinel structure without the formation of secondary phase and morphology analysis reveals the formation of spherical nanoparticles of 6–11 nm size. Additionally, the optical, magnetic and rheological properties of the ferrofluids are investigated in depth. The optical measurement results demonstrate shift in band edge positions to blue region with decrease in particle size because of the quantum confinement effect. Magnetic measurements using SQUID studies illustrate the decrease in saturation magnetization from 56.4 emu/g to 41.08 emu/g, with increase in the concentration of the cobalt dopant. Faraday rotation of CoxFe1−xFe2O4 ferrofluids is measured depending on the different concentrations of cobalt in applied magnetic field. Finally the influence of magnetic field on the viscosity of Co2+ substituted magnetite ferrofluids are investigated, and a deep investigation is done by correlating the experimental details with theoretical modelling like Langevin fitting. Ultimately, the cobalt substitution in ferrofluids reports a smart tuning strategy to change the magneto-optical and magneto-rheological properties of the materials, for making them suitable in medicinal therapy. Other Information Published in: Results in Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rinma.2023.100382